2012
DOI: 10.2174/156720212803530627
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Endoplasmic Reticulum Stress-Induced CHOP Protects Microvasculature Post-Spinal Cord Injury

Abstract: Trauma introduces damaging stressors that compromise protein, lipid, and nucleic acid integrity. Aggregates of unfolded and misfolded proteins in the endoplasmic reticulum (ER) triggers the ER stress response (ERSR)/unfolded protein response (UPR) leading to activation of three signaling pathways mediated by PERK, ATF6, and IRE1. Initially, the ERSR/UPR is pro-homeostatic as it globally slows translation while increasing translation of chaperone proteins and inducing ER-associated degradation. If the cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Excessive ER stress may lead to apoptosis by activating CHOP and Cleaved-Caspase12, resulting in secondary injury after SCI [12, 39]. Previous study has reported that following contusive SCI, CHOP deficiency in mice significantly preserves microvascular density and attenuated macrophage infiltration when compared to wild type mice [40]. Consistent with the prior study, our present study has also found that ER stress was significantly induced by SCI and 4-PBA treatment, a classical ER stress inhibitor, ameliorated the effect of SCI on BSCB permeability and the loss of AJ and TJ proteins, which also been found in a TG-treated HBMVEC model in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ER stress may lead to apoptosis by activating CHOP and Cleaved-Caspase12, resulting in secondary injury after SCI [12, 39]. Previous study has reported that following contusive SCI, CHOP deficiency in mice significantly preserves microvascular density and attenuated macrophage infiltration when compared to wild type mice [40]. Consistent with the prior study, our present study has also found that ER stress was significantly induced by SCI and 4-PBA treatment, a classical ER stress inhibitor, ameliorated the effect of SCI on BSCB permeability and the loss of AJ and TJ proteins, which also been found in a TG-treated HBMVEC model in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a lysosome-dependent essential cellular catabolic pathway that serves to degrade cytoplasmic proteins, protein aggregates and organelles [23, 41]. There are some evidences reported that moderate autophagy protect ECs against cell injury under stressful circumstances [24, 32, 4245].…”
Section: Discussionmentioning
confidence: 99%
“…CD36 activation induces apoptosis in endothelial cells (Jimenez et al, 2000), and we observed a decrease in vascular CHOP expression following injury in CD36 −/− mice. CHOP −/− mice exhibit improved vascular sparing and functional recovery following SCI (Fassbender et al, 2012; Ohri et al, 2011). Alternatively, CD36 −/− mice may exhibit an earlier angiogenic response following injury.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in heterodomain macrophages in CD36 −/− mice may therefore result from a combination of reduced chemokine release and defective macrophage chemotactic responses following SCI. CHOP −/− mice exhibit improved vascularity and reduced macrophage infiltration following injury (Fassbender et al, 2012). Lower ERSR-induced apoptosis in these mice may lead to less inflammation and reduced production of macrophage-recruiting chemokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation